Esophageal and Gastric Disorders in Infancy and Childhood - Till, Holger; Thomson, Mike; Foker, John E.; Holcomb III, George W.; Khan, Khalid M. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Esophageal Gastric and Disorders in Infancy and Childhood includes a wide spectrum of different diseases. These range from congenital malformations such as esophageal atresia (EA), necessitating an experienced team of pediatric surgeons and neonatologists immediately after birth, up to gastro-esophageal reflux disease in elder children, necessitating the pediatric gastroenterologist and visceral surgeon. In the last few years some fascinating pediatric surgical techniques have evolved, such as the thoracoscopic correction of EA or the FOKER technique for elongation in cases of long-gap EA. Prof. Foker has developed this special traction technique and is one of the world's leading experts in long-gap EA. Moreover Prof. Thomson's has established the gold standard of minimally invasive endoscopic treatments for reflux in childhood. This book aims to bring all specialities and experts in pediatric gastroenterology and surgery together.
Keywords: Medicine.; Maternal and child health services.; Gastroenterology.; Nursing.; Minimally invasive surgery.; Pediatric surgery.; elektronické knihy; electronic books